Formaldehyde emission and properties of comprenated wood treated with low molecular weight phenol formaldehyde with addition of urea - Mohd Ali, Rabi'atol Adawiah (2012)
Phenol formaldehyde (PF) resin impregnation and compression at considerable high hot pressing pressure of jelutong and sesenduk is attractive for the improvement of strength properties,dimensional stability and decay durability. The formaldehyde emission (FE) from the treated materials is, however, very high especially when low molecular weight resin is used. Attempt to reduce the formaldehyde emission was made by introducing urea in the treating solution. In this study, urea was used to scavenge the excess formaldehyde produce from the PF-compregnated wood. The urea was preferable as scavenger since it is efficient in reducing formaldehyde emission and low manufacturing cost. The experimental design of this study included impregnation of jelutong (Dyera costulata) and sesenduk (Endospermum diadenum) strips with 20 %, 30 % and 40 % low molecular weight phenol formaldehyde (LmwPF, Mw 600) mixed separately with urea (30% based on solid PF),pre-curing at 60oC for certain periods (7 h, 8 h and 9 h) and subsequently compressed to a compression ratio (CR) of 80 % in a hot press temperature of 150oC for 20 min. The formaldehyde emission, physical and mechanical properties and durability of the compreg wood for each treatment combination was analyzed. Addition of urea into PF resin successfully reduced formaldehyde emission by 97 % for both compreg woods. The results also showed the dimensional stability of the compreg jelutong and sesenduk increased by 60 % and 52 % in anti swelling efficiency (ASE),respectively. When compared between strips treated with and without the presence of urea, the efficiency in preventing swelling of compregs treated with PF solution admixed with urea was more successful. Based on the compreg properties evaluated, the optimum treatment combination of fabricating jelutong and sesenduk was using 30 % PF mixed with 30% urea (based on solid PF),precuring at 60oC for 8 h followed by compressing to 80 % CR at 1500C for 20 min. This treatment combination was then applied to produce compreg laminates. Three layers laminated compreg jelutong and sesenduk were fabricated by assembling the impregnated strips perpendicular (cross) or parallel to each other, followed by compression in a hot press. Compared to the untreated solid wood of the same size, both parallel and cross laminated compreg wood had superior properties. The density of the compreg wood increased by 78 % to 117 % from its original densities. The modulus of rupture (MOR) and modulus of elasticity (MOE) were increased by 24 %, except for the parallel laminates of sesenduk which had lower values than the untreated solid wood. The study also revealed that shear strength at the bonding glueline was higher for the parallel than for the cross laminated compreg wood. Parallel compreg laminates had bonding shear strength comparable to that of solid wood. The treatment used in the study also rendered compreg laminates to be highly resistance towards towards white rot fungus (Pycnoporous sanguineus).